Assessing the Suitability of Online Interactive Tutorials (Web-Learning) for Exploring Mathematical Sequences and Series - Mucti, Alfian; Hermansyah, Hermansyah (JDIME: Journal of Development and Innovation in Mathematics Education, 2023)
Learning media plays a significant role in enhancing the effectiveness and interactivity of mathematics education. This study aims to evaluate the feasibility of Web-based Mathematics Learning Media on sequences and series for 11th-grade high school students in Tarakan. The research method employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate). Survey and questionnaire instruments were used to collect data from experts in media design, subject matter experts, and student responses. The evaluation from the media design experts indicated that the learning media had very high feasibility, with an average score of 86.8%. Similarly, the assessment by subject matter experts deemed it highly feasible, obtaining an average score of 92.50%. Student responses to the learning media indicated an acceptable criterion with an average score of 75%. Based on these evaluations, it can be concluded that the web-based learning media is aligned with the development stage and has sufficient feasibility to be used as a mathematics learning tool for sequences and series in 11th-grade Vocation high school in Tarakan. Consequently, it serves as a solution for implementing mathematics education that leverages technological access.